A percepção de pais sobre a educação em saúde no ambiente escolar - SOUZA, Thais Cristina Flexa (2020)
The family should be the focus of primary care, enabling to open spaces for health education, extinguishing the look that individualizes the care of this structure. In this way, it is important that the family group be contextualized in the multiple dimensions of the health-disease process. The objective of this study is to identify parents' perceptions regarding health education performed by health professionals in the school environment. This is a descriptive qualitative study. The study was performed at the Escola Municipal Parque Amazônia in the neighborhood of Terra Firme, Belém, Pará, Brazil. It participated 15 parents or guardians of regularly enrolled students. All the interviewees were female, aged between 27 and 62 years old. Parents pointed the need of guidance for themselves and their families and recognized the importance of health professionals in assisting students. Also they mentioned the importance of several health professionals, especially doctors and nurses. They reported shyness and embarrassment in talking about sexuality in the home and indicate the health professional as more competent to address the issue. They explained that children and adolescents are disseminators of health knowledge in the family and that health education in the school environment modifies family behaviors. They mentioned the need for continuity of the university extension project in the community, since they recognize the social vulnerability they live in. After this study, it was possible to affirm that health education within the school environment is an effective method to teach good practices for disease prevention and to promote health. It is necessary that the health policies in the school existing be put into practice assiduously so that a good result can be achieved both for the students and for their families.